2005
DOI: 10.1093/hmg/ddi165
|View full text |Cite
|
Sign up to set email alerts
|

Huntingtin phosphorylation on serine 421 is significantly reduced in the striatum and by polyglutamine expansion in vivo

Abstract: Huntington disease (HD) results from polyglutamine expansion in the huntingtin protein (htt). Despite the widespread tissue expression pattern of htt, neuronal loss is highly selective to medium spiny neurons of the striatum. Huntingtin is phosphorylated on serine-421 (S421) by the pro-survival signaling protein kinase Akt (PKB) and this has been previously shown to be protective against the toxicity of polyglutamine-expanded htt in cell culture. Using an antibody specific for htt phosphorylated on S421, we no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
108
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(116 citation statements)
references
References 40 publications
8
108
0
Order By: Relevance
“…12 However, Akt activation status in 6-month-old YAC128 mice and in 6-and 10-week-old R6/2 mice was previously shown to be unchanged. 36 Our observation that the activation of the Akt pathway in the presence of mhtt is a brain region-dependent effect explains why that study failed to find changes in pAkt (Ser473) levels as active Akt was measured in whole brain lysates. 36 Akt activation has been largely shown as one of the main mechanisms to prevent neuronal death during injury.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…12 However, Akt activation status in 6-month-old YAC128 mice and in 6-and 10-week-old R6/2 mice was previously shown to be unchanged. 36 Our observation that the activation of the Akt pathway in the presence of mhtt is a brain region-dependent effect explains why that study failed to find changes in pAkt (Ser473) levels as active Akt was measured in whole brain lysates. 36 Akt activation has been largely shown as one of the main mechanisms to prevent neuronal death during injury.…”
Section: Discussionmentioning
confidence: 83%
“…36 Our observation that the activation of the Akt pathway in the presence of mhtt is a brain region-dependent effect explains why that study failed to find changes in pAkt (Ser473) levels as active Akt was measured in whole brain lysates. 36 Akt activation has been largely shown as one of the main mechanisms to prevent neuronal death during injury. 8 Accordingly, Akt prevents neuronal death induced by mhtt, 14 and increasing Akt expression has beneficial effects in Drosophila models of HD.…”
Section: Discussionmentioning
confidence: 83%
“…Akt activation is an early pro-survival striatal response in knock-in Hdh Q111 mice and STHdh Q111/Q111 cells [28]; importantly, activation of IGF-1/Akt pathway caused Htt phosphorylation at Ser421, decreasing mHtt nuclear inclusions and mHtt toxicity [27] and regulated anterograde and retrograde transport defects in HD cortical neurons [78]. Another study demonstrated that p-(Ser473)Akt was unchanged in YAC128 and in R6/2 HD mice, but the levels of p-(Ser421)Htt were decreased in the striatum of YAC128 mice and in cells expressing mHtt [79]. In contrast, insulin receptor substrate (IRS)-2, which activates PI-3K/Akt and mTOR cascade, promoted mitochondrial dysfunction and oxidative stress in R6/2 mice; however, in the same study, the authors showed that IRS-2 protein levels were unchanged in the striatum of patients with grade II HD [80].…”
Section: Discussionmentioning
confidence: 98%
“…Htt is itself a phosphoprotein with a toxicity when mutated that is regulated by phosphorylation (Humbert et al, 2002;Rangone et al, 2004;Luo et al, 2005;Warby et al, 2005;Pardo et al, 2006;Schilling et al, 2006). Cdk5 phosphorylates htt at S434 and regulates its proteolysis (Luo et al, 2005).…”
Section: Cdk5 Phosphorylates Huntingtin At Serines 1181 and 1201 In Vmentioning
confidence: 99%
“…In disease, polyQ expansion in htt leads to a reduction of BDNF transcription and transport, thereby reducing neurotrophic support (Zuccato et al, 2001;Gauthier et al, 2004). Arguments for a key role of the protein context in pathogenesis also come from the observations that cleavage and posttranslational modifications regulate the toxicity of polyQ-htt (Humbert et al, 2002; (Humbert et al, 2002;Warby et al, 2005;Pardo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%